Thermal Environment in Underground Mining Activities: An Integrated Approach - António Sousa (2012)
In underground mining the thermal environment is a growing problem when the depth increases. In this context, this paper seeks to present a new approach to quantify the relationship between thermal environment, safety conditions, health and productivity. For that, an objective function has been designed in a cost minimization perspective. The function provides the best parameters set for the operation of ventilation systems, ensuring the most appropriate working conditions. The used units (currency) allow obtaining results that provides a comprehensive analysis of the economic impact.